2015
DOI: 10.1016/j.jpedsurg.2014.10.028
|View full text |Cite
|
Sign up to set email alerts
|

An extracorporeal artificial placenta supports extremely premature lambs for 1week

Abstract: Purpose The treatment of extreme prematurity remains an unsolved problem. We developed an artificial placenta (AP) based on extracorporeal life support (ECLS) that simulates the intrauterine environment and provides gas exchange without mechanical ventilation (MV), and compared it to the current standard of neonatal care. Methods Extremely premature lambs (110-120d; term=145d) were used. AP lambs (n=9) were cannulated (jugular drainage, umbilical vein reinfusion) for ECLS .Control lambs (n=7) were intubated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 27 publications
1
59
0
Order By: Relevance
“…They report support of extreme premature lambs in relatively stable physiologic condition for up to 1 week495051 with average circuit flows of 87.4±17.9 ml kg −1  min −1 . They also report the requirement for vasopressors for the first 3 days, sedation throughout the run and findings of closure of the ductus venosus on necropsy, with the development of ascites and pleural effusions.…”
Section: Discussionmentioning
confidence: 93%
“…They report support of extreme premature lambs in relatively stable physiologic condition for up to 1 week495051 with average circuit flows of 87.4±17.9 ml kg −1  min −1 . They also report the requirement for vasopressors for the first 3 days, sedation throughout the run and findings of closure of the ductus venosus on necropsy, with the development of ascites and pleural effusions.…”
Section: Discussionmentioning
confidence: 93%
“…Although the umbilical arteries comprise the most physiological conduit for extracorporeal support of the preterm neonate, attempts to cannulate the umbilical vessels for 'artificial placenta' inflow over the past 50 years have produced limited and progressively declining driving pressures and inadequate circuit flows. Researchers have employed several strategies aiming to circumvent the inherent spasticity of umbilical vessels, such as using continuous paralytics to minimize flow-limiting movement, inserting umbilical cannulas to the depth of the abdominal aorta and incorporating pumps to augment flow, often avoiding the umbilical arteries altogether (Callaghan et al 1965;Alexander et al 1968;Zapol et al 1969;Unno et al 1993;Awad et al 1995;Sakata et al 1998;Pak et al 2002;Reoma et al 2009;Miura et al 2012;Schoberer et al 2014;Bryner et al 2015;Miura et al 2015). Although many of these approaches have supported long-term extra-uterine runs in premature animal models, none have achieved physiological 'placental' flows.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 50 years, vascular access has been an obstacle for groups developing 'artificial placenta' technology, with long-term support generally limited by insufficient circuit flows and, ultimately, subphysiological oxygen delivery (Callaghan et al 1965;Alexander et al 1968;Zapol et al 1969;Unno et al 1993;Awad et al 1995;Sakata et al 1998;Pak et al 2002;Reoma et al 2009;Miura et al 2012;Schoberer et al 2014;Bryner et al 2015;Miura et al 2015). As our system evolved, we experimented with three distinct AV cannulation strategies: carotid artery/jugular vein (CA/JV), carotid artery/umbilical vein (CA/UV) and umbilical artery (×2)/umbilical vein (UA/UV).…”
Section: Introductionmentioning
confidence: 99%
“…This EGA was selected as lung development at this stage is analogous to that of a 24-week human fetus. [9] Ten-14Fr cannulas (Terumo: Ann Arbor, MI) were placed in the right jugular vein (drainage) and umbilical vein (reinfusion), and the circuit was completed using ¼″ tubing (Tygon: Lima, OH), a roller pump (M-pump, MC3: Ann Arbor, MI), and oxygenator/heat exchanger (either Capiox Baby Rx, Terumo: Ann Arbor MI, or Medos HiLite, Xenios: Heilbronn, Germany; Figure 1). Venovenous (VV) ECLS was initiated.…”
Section: Methodsmentioning
confidence: 99%
“…Given that pulmonary morbidity decreases with increasing gestational age[2], the goal of the AP is to allow premature lungs to develop to the point where they can provide adequate gas exchange to support the neonate. We have previously demonstrated that the AP can support otherwise moribund premature lambs for over seven days[9], and that lung development continues during this support. [10,11]…”
Section: Introductionmentioning
confidence: 99%